Innovate or exploit? Unveiling the international entrepreneurial odyssey through the lens of status quo bias - Faroque, A.R.; Shimul, Anwar Sadat; Xu, H.; Kuivalainen, O.; Murshed, F.; Sundqvist, S. (2025)
We contribute novel insights into how status quo bias may play a part in identifying and capitalizing on international opportunities, thus addressing a previously overlooked aspect of cognitive perspective in international entrepreneurship research. First, from an entrepreneurial process perspective, we assert that internationalizing firms can attain a performance advantage by adopting Kirznerian and Schumpeterian types of entrepreneurial orientation (EO) with the mediation of opportunity recognition and exploitation. Building on cognitive bias theory, we further posit that status quo bias plays a significant role in shaping the relationship between EO and opportunity recognition and exploitation. We test our hypotheses using survey data collected from 275 internationalizing firms. The empirical results suggest that EO variants exhibit distinct influences and are influenced in unique ways by international opportunity recognition, exploitation and status quo bias. Specifically, we find that a higher level of status quo bias strengthens the relationship between Schumpeterian EO and opportunity recognition, whereas a lower level strengthens the association between Schumpeterian EO and opportunity exploitation. However, no significant effect of status quo bias is found in Kirznerian firms. The study offers both theoretical and practical implications, and provides valuable recommendations for future research.